Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
[tex]f(t)=t^4+t^2-5\\
\\
f(b)-f(-b)=b^4+b^2-5-[(-b)^4+(-b)^2-5]\\
\\
f(b)-f(-b)=b^4+b^2-5-b^4-b^2+5\\
\\
\boxed{f(b)-f(-b)=0}
[/tex]
[tex]f(b)-f(-b)=b^4+b^2-5-((-b)^4+(-b)^2-5)\\
f(b)-f(-b)=b^4+b^2-5-(b^4+b^2-5)\\
f(b)-f(-b)=b^4+b^2-5-b^4-b^2+5\\
f(b)-f(-b)=0
[/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.